High-strength aluminum-based alloy material and production process thereof

By using the sol-gel method to prepare nanostrengthening agent and zirconium elements in aluminum-based alloy materials, the problem of poor mechanical properties of additively manufactured aluminum alloy materials during laser molding is solved, and high strength, excellent fatigue resistance and high density are achieved.

CN119876706AActive Publication Date: 2025-04-25JIANGSU VILORY ADVANCED MATERIALS TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510368507.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

The existing additively manufactured aluminum alloy materials have poor mechanical properties during laser forming, which are prone to thermal crack defects, and the high content of added Mg leads to high porosity of the material, affecting density and fatigue properties.

Method used

The nanostrengthening agent ZrOCl2·8H2O and precipitant were prepared by the sol-gel method, and the dispersion strengthening agent was added to the aluminum-based alloy to form a dispersion strengthening agent, which hindered the development of microcracks and promoted grain refinement. At the same time, zirconium elements were used to replace part of the magnesium elements, reducing the grain size and improving mechanical properties.

Benefits of technology

The tensile strength, yield strength and elongation of aluminum-based alloy materials have been significantly improved, with excellent comprehensive performance, mechanical properties reaching more than 625MPa, yield strength above 597MPa, and elongation >20%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum alloy materials, and particularly relates to a high-strength aluminum-based alloy material and a production process thereof. The high-strength aluminum-based alloy material provided by the invention comprises 1.0%-3.2% of magnesium, 1.0%-2.7% of zirconium, 1.25%-1.53% of manganese, 0.8%-1.4% of copper, 0.2%-0.5% of vanadium, 0.7%-1.0% of a nano reinforcing agent and the balance of aluminum. According to the invention, the formula of the aluminum-based alloy material is optimized, the ZrOCl2. 8H2O aqueous solution and the precipitant are adopted to prepare the nano reinforcing agent through a sol-gel method, a dispersion reinforcing agent is formed in the aluminum-based alloy material and plays a pinning role, the development of microcracks is effectively hindered, the grain refinement is promoted, and the mechanical property of the alloy is enhanced. According to the high-strength aluminum-based alloy material, the tensile strength is larger than 625 MPa, the yield strength is larger than 597 MPa, the ductility is larger than 20%, and the comprehensive performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy materials, and in particular relates to a high-strength aluminum-based alloy material and a production process thereof. Background Art

[0002] Aluminum alloy is an alloy with aluminum as the matrix and a certain amount of other alloying elements added. It is one of the light metal materials with high strength, good casting performance and plastic processing performance, good electrical and thermal conductivity, good corrosion resistance and weldability. It can be used as a structural material and is used in aerospace, aviation, transportation, construction, electromechanical, light chemical industry and daily necessities.

[0003] Among the aluminum alloy materials for additive manufacturing that can be maturely applied at present, only some Al-Si alloys and a very small number of Al-Mg alloys can be laser additively formed. However, the Al-Si alloy is affected by the material system and the inherent solid solubility of elements in the aluminum alloy, and the material performance is not excellent enough. Although the Al-Mg alloy has good strength, the Mg content added during the forming process is very high due to the pursuit of high strength, resulting in the formation of a large amount of volatile smoke under the bombardment of the laser. The high porosity of the material affects the density of the material. Although the formed material has high strength, it is very easy to fatigue and become unstable, which seriously affects its practical application and promotion. Furthermore, the Al-Mg alloys currently used are all strengthened by Sc, that is, the Al-Mg-Sc system. The high price of raw materials also limits the application and promotion of the material.

[0004] The effects of developing new aluminum alloy materials by traditional preparation methods, such as improving alloy purity, adjusting composition, changing heat treatment specifications, etc., have become increasingly smaller. In order to significantly improve the strength, corrosion resistance, heat resistance, fracture toughness and other properties of the material, the aluminum alloy melt is atomized, quickly solidified into powder, and then the powder is pressed, sintered, and pressure-processed into aluminum alloy materials. The obtained material has fine grains, refined intermetallic compound particles, uniform chemical composition, increased supersaturated solid solubility of alloy elements, and comprehensive utilization of dispersion strengthening, solid solution strengthening and aging strengthening. Therefore, the material has high strength and good stress corrosion resistance. However, the aluminum alloy powder currently produced is basically atomized by inert gas or centrifugal atomization. The obtained aluminum alloy powder particles have low dispersion and are easy to stick together. Usually, lubricating adhesives such as paraffin and zinc stearate are added to promote powder molding, but this operation will introduce impurities into the aluminum alloy powder, affecting the strength of the material.

[0005] The Chinese patent application document with publication number CN109954884A discloses a method for charging and molding high-strength and hard-to-deform aluminum alloy powder by powder metallurgy, which is as follows: the aluminum alloy powder is pre-treated by mechanical ball milling and then soaked in anhydrous ethanol, then loaded into a powder loading device, pressed by a hydraulic press, and wrapped with a welding cover and a degassing aluminum tube, and finally heated to remove the residual ethanol in the wrapping to obtain a powder blank. This method omits the step of cold isostatic pressing of the powder, shortening the production cycle, but the aluminum alloy powder used is gas atomized powder, and the dispersion of the aluminum alloy powder is low and it is easy to stick. Summary of the invention

[0006] In order to solve the technical problem of poor mechanical properties existing in the related art, the purpose of the present invention is to provide a high-strength aluminum-based alloy material and a production process thereof.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows: A high-strength aluminum-based alloy material, comprising the following components by mass percentage: 1.0%-3.2% of magnesium, 1.0%-2.7% of zirconium, 1.25%-1.53% of manganese, 0.8%-1.4% of copper, 0.2%-0.5% of vanadium, 0.7%-1.0% of nano-strengthener and the balance of aluminum; the nano-strengthener is prepared from ZrOCl2·8H2O and a precipitant by a sol-gel method.

[0008] The alloying element content of traditional additively manufactured aluminum alloys is high. During the laser additive manufacturing process, the internal stress of the molded parts is large due to the high temperature gradient inside the molten pool and the fast solidification rate, which easily causes thermal crack defects and reduces the mechanical properties. The nano-strengthening agent with nano effect used in the present invention is easier to be evenly dispersed in the aluminum alloy matrix, forming a dispersion strengthener and playing a pinning role, effectively hindering the development of microcracks and promoting grain refinement, further enhancing the mechanical properties of the alloy.

[0009] In aluminum-magnesium alloys suitable for additive manufacturing, the content of magnesium is relatively high, but magnesium will volatilize during the 3D printing process, generating a large amount of black smoke and forming holes on the surface of the aluminum alloy, thereby reducing the yield strength of the aluminum alloy. In the present invention, zirconium is used to replace part of the magnesium element. The addition of zirconium promotes the formation of Al3Zr precipitation phase, generates grain boundary pinning, and acts as a non-uniform nucleation point in the aluminum alloy, which can effectively reduce the grain size of the aluminum alloy, thereby reducing the sensitivity of the aluminum alloy to cracks and improving the mechanical strength. Vanadium has a low diffusion rate in aluminum alloys, which can enhance the high-temperature strength of aluminum alloys. At the same time, vanadium can form intermetallic compounds with aluminum through eutectic reaction in aluminum alloys, which has the effect of refining grains, increasing recrystallization temperature, and improving mechanical properties.

[0010] Furthermore, the preparation method of the nano-strengthener is specifically as follows: (1) adding ZrOCl2·8H2O aqueous solution and ammonia water to a precipitant solution at the same time, stirring for reaction, standing for aging, and obtaining Zr(OH)4 gel; (2) filtering and washing the Zr(OH)4 gel obtained in step (1) to obtain Zr(OH)4 hydrogel; (3) adding anhydrous ethanol to the Zr(OH)4 hydrogel obtained in step (2), stirring, filtering, drying, grinding, and heating under the condition of introducing nitrogen for heat treatment, cooling, and grinding to obtain the nano-strengthener.

[0011] In the present invention, a ZrOCl2·8H2O aqueous solution and a precipitant are used to prepare zirconium oxide nanopowder by a sol-gel method, and the particle size and specific surface area of ​​the zirconium oxide nanopowder are further controlled by controlling the temperature and time of heat treatment. It is found that when the heat treatment temperature is too high or the time is too long, the larger the particle size of the obtained zirconium oxide nanopowder, the smaller the specific surface area. In addition, in the present invention, anhydrous ethanol is added to the hydrogel to replace the water in the hydrogel to form an alcohol gel, and heat treatment is performed under the condition of flowing nitrogen, which can effectively take away the water in the gel, avoid hard agglomeration of the zirconium oxide nanopowder, and is conducive to preparing nanometer-sized zirconium oxide nanoparticles.

[0012] Furthermore, in the preparation method of the nano-enhancer, the concentration of the ZrOCl2·8H2O aqueous solution in step (1) is 0.1-0.2 mol / L, the pH value of the ammonia water is 9-10, the dropping speed of the ZrOCl2·8H2O aqueous solution and the ammonia water is 2.8-3.2 mL / min, the precipitant is an ammonia aqueous solution with a mass percentage of 2.5%-3.0%, the stirring reaction time is 2-2.5 h, and the static aging time is 8-10 h.

[0013] Furthermore, in the step (3) of the preparation method of the nano-strengthening agent, the heat treatment temperature is 400-450° C., and the heat treatment time is 3.8-4.3 h.

[0014] Furthermore, the mass fractions of the components in the preparation method of the nano-strengthener are: 20-30 parts of ZrOCl2·8H2O aqueous solution, 10-16 parts of ammonia water, 10-15 parts of precipitant solution, and 8-12 parts of anhydrous ethanol.

[0015] Furthermore, the high-strength aluminum-based alloy material includes the following components, by mass percentage: 2.4% magnesium, 1.9% zirconium, 1.35% manganese, 1.1% copper, 0.4% vanadium, 0.9% nano-strengthener and the balance aluminum.

[0016] The present invention also provides a production process of the high-strength aluminum-based alloy material, comprising the following steps: S1: adding each component in the high-strength aluminum-based alloy material formula into a melting furnace, heating and melting under the protection of an inert gas to obtain a metal solution; S2: The metal solution obtained in step S1 is vacuum atomized by an inert gas to obtain a high-strength aluminum-based alloy material.

[0017] Furthermore, the inert gas in step S1 and step S2 of the production process of the high-strength aluminum-based alloy material is helium or argon, and the pressure of the inert gas added into the melting furnace in step S1 is 2.4-3.0 MPa.

[0018] In the present invention, the volatilization of elements in the aluminum-based alloy material is reduced by controlling the pressure in the melting furnace.

[0019] Furthermore, the heating and melting temperature in step S1 of the production process of the high-strength aluminum-based alloy material is 1250-1400°C.

[0020] Furthermore, in the production process step S2 of the high-strength aluminum-based alloy material, the flow rate of the metal solution is 10-15 g / s.

[0021] Compared with the prior art, the high-strength aluminum-based alloy material and its production process provided by the present invention have the following technical advantages: (1) The present invention optimizes the formula of aluminum-based alloy materials, effectively reduces the grain size of aluminum alloys, and improves mechanical strength; (2) In the present invention, a nano-strengthening agent is prepared by a sol-gel method using a ZrOCl2·8H2O aqueous solution and a precipitant, which forms a dispersion strengthening agent in the aluminum-based alloy material and plays a pinning role, effectively hindering the development of microcracks and promoting grain refinement, further enhancing the mechanical properties of the alloy; (3) The high-strength aluminum-based alloy material provided by the present invention has a tensile strength greater than 625 MPa, a yield strength greater than 597 MPa, an elongation greater than 20%, and excellent comprehensive performance. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. Those skilled in the art can make various modifications based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the scope of the present invention.

[0023] Example 1 A high-strength aluminum-based alloy material, comprising the following components by mass percentage: 1.0% magnesium, 2.7% zirconium, 1.25% manganese, 0.8% copper, 0.2% vanadium, 0.7% nano-strengthener and the balance aluminum.

[0024] The preparation method of the nano-strengthener is specifically as follows: (1) 20 g of a 0.1 mol / L ZrOCl2·8H2O aqueous solution and 10 g of ammonia water with a pH value of 9 are simultaneously added dropwise at a rate of 2.8 mL / min to 10 g of a 2.5% ammonia aqueous solution, stirred for reaction for 2 h, and aged for 8 h to obtain a Zr(OH)4 gel; (2) the Zr(OH)4 gel obtained in step (1) is filtered and washed until no chloride ions are contained in the washing liquid to obtain a Zr(OH)4 hydrogel; (3) 8 g of anhydrous ethanol is added to the Zr(OH)4 hydrogel obtained in step (2), stirred for 2 h, filtered, and the filter cake obtained is placed in a vacuum drying oven and dried at 100°C for 24 h, taken out and ground into powder, heated to 400°C for heat treatment for 3.8 h under the condition of nitrogen, cooled, and ground to obtain a nano-strengthener.

[0025] The production process of high-strength aluminum-based alloy material includes the following steps: S1: Add the components in the high-strength aluminum-based alloy material formula into a melting furnace, evacuate and introduce helium or argon, maintain the pressure in the melting furnace at 2.4 MPa, heat to 1250°C to melt, and obtain a metal solution; S2: The metal solution obtained in step S1 is vacuum atomized by an inert gas at a flow rate of 10 g / s to obtain a high-strength aluminum-based alloy material.

[0026] Example 2 A high-strength aluminum-based alloy material, comprising the following components by mass percentage: 3.2% magnesium, 1.0% zirconium, 1.53% manganese, 1.4% copper, 0.5% vanadium, 1.0% nano-strengthener and the balance aluminum.

[0027] The preparation method of the nano-strengthener is specifically as follows: (1) 30 g of a 0.2 mol / L ZrOCl2·8H2O aqueous solution and 16 g of ammonia water with a pH value of 10 are simultaneously added dropwise at a rate of 3.2 mL / min to 15 g of a 3.0% ammonia aqueous solution, stirred for reaction for 2.5 h, and allowed to stand for aging for 10 h to obtain a Zr(OH)4 gel; (2) the Zr(OH)4 gel obtained in step (1) is filtered and washed until no chloride ions are contained in the washing liquid to obtain a Zr(OH)4 hydrogel; (3) 12 g of anhydrous ethanol is added to the Zr(OH)4 hydrogel obtained in step (2), stirred for 2 h, filtered, and the filter cake obtained is placed in a vacuum drying oven and dried at 100°C for 24 h, taken out and ground into powder, heated to 450°C for heat treatment for 4.3 h under the condition of nitrogen, cooled, and ground to obtain a nano-strengthener.

[0028] The production process of high-strength aluminum-based alloy material includes the following steps: S1: Add the components in the high-strength aluminum-based alloy material formula into a melting furnace, evacuate and introduce helium or argon, maintain the pressure in the melting furnace at 3.0 MPa, heat to 1400°C to melt, and obtain a metal solution; S2: The metal solution obtained in step S1 is vacuum atomized by an inert gas at a flow rate of 15 g / s to obtain a high-strength aluminum-based alloy material.

[0029] Example 3 A high-strength aluminum-based alloy material, comprising the following components by mass percentage: 2.4% magnesium, 1.9% zirconium, 1.35% manganese, 1.1% copper, 0.4% vanadium, 0.9% nano-strengthener and the balance aluminum.

[0030] The preparation method of the nano-strengthener is specifically as follows: (1) 26 g of a 0.15 mol / L ZrOCl2·8H2O aqueous solution and 13 g of ammonia water with a pH value of 9.5 are simultaneously added dropwise at a rate of 3.0 mL / min to 12 g of a 2.8% ammonia aqueous solution, stirred for reaction for 2.2 h, and allowed to stand for aging for 9.2 h to obtain a Zr(OH)4 gel; (2) the Zr(OH)4 gel obtained in step (1) is filtered and washed until no chloride ions are contained in the washing liquid to obtain a Zr(OH)4 hydrogel; (3) 10 g of anhydrous ethanol is added to the Zr(OH)4 hydrogel obtained in step (2), stirred for 2 h, filtered, and the filter cake obtained is placed in a vacuum drying oven and dried at 100°C for 24 h, taken out and ground into powder, heated to 430°C for heat treatment for 4.0 h under the condition of nitrogen, cooled, and ground to obtain a nano-strengthener.

[0031] The production process of high-strength aluminum-based alloy material includes the following steps: S1: Add the components in the high-strength aluminum-based alloy material formula into a melting furnace, evacuate and introduce helium or argon, maintain the pressure in the melting furnace at 2.8MPa, heat to 1310°C to melt, and obtain a metal solution; S2: The metal solution obtained in step S1 is vacuum atomized by an inert gas at a flow rate of 13 g / s to obtain a high-strength aluminum-based alloy material.

[0032] Comparative Example 1 The formula and preparation method of the aluminum-based alloy material in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that an equal amount of magnesium is used instead of zirconium in this comparative example.

[0033] Comparative Example 2 The formula and preparation method of the aluminum-based alloy material in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that an equal amount of aluminum is used instead of vanadium in this comparative example.

[0034] Comparative Example 3 The formula and preparation method of the aluminum-based alloy material in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that an equal amount of aluminum is used to replace manganese in this comparative example.

[0035] Comparative Example 4 The formula and preparation method of the aluminum-based alloy material in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that an equal amount of aluminum is used to replace the nano-strengthening agent in this comparative example.

[0036] Comparative Example 5 The formula and preparation method of the aluminum-based alloy material described in this comparative example are similar to those of Example 3. The difference between this comparative example and Example 3 is that the heat treatment temperature in the preparation method of the nano-strengthener in this comparative example is 600° C. and the heat treatment time is 4.5 h.

[0037] Comparative Example 6 The formula and preparation method of the aluminum-based alloy material in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that an equal amount of deionized water is used instead of anhydrous ethanol in the preparation method of the nano-strengthening agent in this comparative example.

[0038] Comparative Example 7 The formula and preparation method of the aluminum-based alloy material described in this comparative example are similar to those of Example 3. The difference between this comparative example and Example 3 is that in the production process step S1 of the aluminum-based material in this comparative example, the pressure in the melting furnace is controlled to be 1.0 MPa.

[0039] Test example In this test example, the aluminum-based alloy materials prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were used to prepare aluminum alloy molded parts of 10×10 cm by 3D printing technology, and the yield strength, tensile strength and elongation were tested with reference to GB / T 222-2002 Room Temperature Tensile Test Method for Metallic Materials. The test results are shown in Table 1.

[0040] Table 1 Mechanical properties test results

[0041] As shown in Table 1, the tensile strength of the molded parts made of the high-strength aluminum-based alloy material provided by the present invention is greater than 625MPa, the yield strength is greater than 597MPa, and the elongation is greater than 20%, which shows that the high-strength aluminum-based alloy material provided by the present invention has good mechanical properties. Among them, the aluminum-based alloy material prepared in Example 3 has the best performance in all aspects and is the best embodiment of the present invention.

[0042] Compared with Example 3, in Comparative Example 1, an equal amount of magnesium is used to replace zirconium, but the yield strength of the obtained alloy material is significantly reduced. This is because the magnesium content is too high, which volatilizes during the 3D printing process and forms holes on the surface of the aluminum-based alloy material, resulting in a decrease in yield strength; in Comparative Example 2, an equal amount of aluminum is used to replace vanadium, but the mechanical properties of the obtained alloy material are reduced to varying degrees, which shows that the addition of vanadium can improve the mechanical properties of the aluminum-based alloy material; in Comparative Example 3, an equal amount of aluminum is used to replace manganese, but the mechanical properties of the obtained alloy material are reduced to varying degrees, which shows that the formula of the present invention has been optimized; in Comparative Example 4, an equal amount of aluminum is used to replace the nano-strengthener, but the mechanical properties of the obtained alloy material are significantly deteriorated, which shows that the nano-strengthener is uniformly dispersed in the aluminum alloy matrix, which can play a role of dispersion strengthening and pinning, effectively hinder the development of microcracks, and improve the mechanical properties of the alloy; in the preparation method of the nano-strengthener in Comparative Example 5, the temperature and time of the heat treatment are changed, but the mechanical properties of the prepared alloy material are significantly deteriorated. The mechanical properties of the obtained alloy materials are reduced to varying degrees, which shows that in the preparation process of the nano-strengthener, the temperature and time of the heat treatment are the key to controlling the particle size of the nano-strengthener. If the temperature is too high or the time is too long, the larger the particle size of the obtained nano-strengthener will be, and the uneven dispersion in the alloy material will affect the mechanical properties of the alloy material; in the preparation method of the nano-strengthener in Comparative Example 6, an equal amount of deionized water is used instead of anhydrous ethanol, but the mechanical properties of the obtained alloy material are reduced to varying degrees. This is because in the preparation process of the nano-strengthener, the water in the hydrogel evaporates unevenly or incompletely, resulting in uneven particle size of the nano-strengthener, and the dispersion effect of the nano-strengthener added to the alloy material is weak, resulting in reduced mechanical properties; Comparative Example 7 changes the pressure in the melting furnace in step S1 of the aluminum-based material production process, but the yield strength of the obtained alloy material is reduced, which shows that after changing the pressure in the melting furnace, the magnesium element in the raw material will volatilize, forming holes on the surface of the alloy material, resulting in reduced yield strength.

[0043] The above embodiments are merely illustrative of the preparation method of the present invention, and are not intended to limit the present invention. Any person skilled in the art may not modify the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the technical concept provided by the present invention are still covered by the claims of the present invention.

Claims

1. A high-strength aluminum-based alloy material, characterized in that: Calculated by mass percentage, it includes the following components: 1.0%-3.2% magnesium, 1.0%-2.7% zirconium, 1.25%-1.53% manganese, 0.8%-1.4% copper, 0.2%-0.5% vanadium, 0.7%-1.0% nano-strengthener and the balance aluminum; the nano-strengthener is prepared from ZrOCl2·8H2O and a precipitant by a sol-gel method, and the preparation method is as follows: (1) adding a ZrOCl2·8H2O aqueous solution and ammonia water to a precipitant solution at the same time, stirring the reaction mixture, , standing and aging to obtain Zr(OH)4 gel; (2) filtering and washing the Zr(OH)4 gel obtained in step (1) to obtain Zr(OH)4 hydrogel; (3) adding anhydrous ethanol to the Zr(OH)4 hydrogel obtained in step (2), stirring, filtering, drying, grinding, heating to 400-450°C under nitrogen flow for heat treatment for 3.8-4.3h, cooling, grinding, and obtaining a nano-strengthening agent.

2. The high-strength aluminum-based alloy material according to claim 1, characterized in that: The concentration of the ZrOCl2·8H2O aqueous solution in step (1) is 0.1-0.2 mol / L, the pH value of the ammonia water is 9-10, the dropping speed of the ZrOCl2·8H2O aqueous solution and the ammonia water is 2.8-3.2 mL / min, the precipitant is an ammonia water solution with a mass percentage of 2.5%-3.0%, the stirring reaction time is 2-2.5 h, and the static aging time is 8-10 h.

3. The high-strength aluminum-based alloy material according to claim 1, characterized in that: The mass fractions of the components in the preparation method of the nano-strengthener are: 20-30 parts of ZrOCl2·8H2O aqueous solution, 10-16 parts of ammonia water, 10-15 parts of precipitant solution, and 8-12 parts of anhydrous ethanol.

4. The high-strength aluminum-based alloy material according to claim 1, characterized in that: Calculated by mass percentage, the material includes the following components: 2.4% magnesium, 1.9% zirconium, 1.35% manganese, 1.1% copper, 0.4% vanadium, 0.9% nano-strengthener and the balance aluminum.

5. The production process of the high-strength aluminum-based alloy material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Add the components in the high-strength aluminum-based alloy material formula into a melting furnace, heat and melt them under the protection of inert gas to obtain a metal solution; S2: The metal solution obtained in step S1 is vacuum atomized by an inert gas to obtain a high-strength aluminum-based alloy material.

6. The production process of the high-strength aluminum-based alloy material according to claim 5, characterized in that: The inert gas in step S1 and step S2 is helium or argon. The pressure of the inert gas added into the melting furnace in step S1 is 2.4-3.0 MPa.

7. The production process of the high-strength aluminum-based alloy material according to claim 5, characterized in that: The heating and melting temperature in step S1 is 1250-1400°C.

8. The production process of the high-strength aluminum-based alloy material according to claim 5, characterized in that: The flow rate of the metal solution in step S2 is 10-15 g / s.

Citation Information

Patent Citations

  • Loading forming method of powder metallurgy high-strength difficult-to-deform aluminum alloy powder

    CN109954884A

  • Nanometer zirconia enhanced aluminum magnesium alloy material for automobile electronic packaging and preparing method of nanometer zirconia enhanced aluminum magnesium alloy material

    CN106011550A

  • Ultrahigh-strength cast aluminum alloy hub material ZL350 / 500 and manufacturing technology thereof

    CN113718143A

  • Low-cost high-strength Al-Cu alloy powder material for 3D printing and application of low-cost high-strength Al-Cu alloy powder material

    CN118497571A

  • Heat-resistant high-strength aluminum alloy material for additive manufacturing and preparation method of heat-resistant high-strength aluminum alloy material

    CN119162494A